2018
DOI: 10.1080/1040841x.2018.1467875
|View full text |Cite
|
Sign up to set email alerts
|

Alternative antimicrobials: the properties of fatty acids and monoglycerides

Abstract: With the rising antibiotic resistance of many bacterial species, alternative treatments are necessary to combat infectious diseases. The World Health Organization and the US Centres for Disease Control and Prevention have warned that some infections, such as those from Neisseria gonorrhoeae, may be untreatable within a few years. One avenue of exploration is the use of antimicrobial fatty acids and their derivatives for therapeutic prevention or treatment of bacterial infections. Several studies have explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 67 publications
(92 reference statements)
7
59
0
Order By: Relevance
“…In agreement with the present study, fatty acids were found to affect the viral envelope, with high concentrations causing complete disintegration of viral particles (Thormar et al, 1987, Thormar et al, 1994. In agreement with the present study, previous studies have also reported no antiviral effect of fatty acids on nonenveloped viruses (Thormar et al, 1987, Churchward et al, 2018, indicating that the antiviral mechanism of free fatty acids and ViroSAL may involve the viral envelope and we anticipate that to be due to a surfactant effect (Yoon et al, 2015, Yoon et al, 2017.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with the present study, fatty acids were found to affect the viral envelope, with high concentrations causing complete disintegration of viral particles (Thormar et al, 1987, Thormar et al, 1994. In agreement with the present study, previous studies have also reported no antiviral effect of fatty acids on nonenveloped viruses (Thormar et al, 1987, Churchward et al, 2018, indicating that the antiviral mechanism of free fatty acids and ViroSAL may involve the viral envelope and we anticipate that to be due to a surfactant effect (Yoon et al, 2015, Yoon et al, 2017.…”
Section: Discussionsupporting
confidence: 92%
“…WO 2011/061237) to build and use an emulsion to evaluate its antiviral potential. Recent publications have noted the potential antimicrobial activity of nanoemulsions and microemulsions (Churchward et al, 2018, Buranasuksombat et al, 2011, Ma et al, 2016, Donsi and Ferrari, 2016. In each of these studies there are no data that clearly evaluate the contribution of the individual components to the overall properties which, in a mixed system may be synergistic or antagonistic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antimicrobial properties of fatty acids have been reported extensively in the literature (for a review, see [1,2]). Previously, Thormar et al [3], demonstrated the antiviral effects of 14 different free fatty acids and lipid extracts from human milk against vesicular stomatitis virus (VSV), herpes simplex virus (HSV) and visna virus, revealing that short-chain saturated fatty acids (butyric, caproic and caprylic), together with long-chain saturated fatty acids (palmitic and stearic), had no or very little antiviral activity, whereas medium-chain saturated entities, including capric, lauric, myristic and long-chain unsaturated oleic, linoleic and linolenic acids, were antiviral, albeit at different concentrations.…”
Section: Introductionmentioning
confidence: 99%